Chemical bath deposition of CdS quantum dots on vertically aligned ZnO nanorods for quantum dots-sensitized solar cells - Lee, Wonjoo; Min, Sun Ki; Dhas, Vivek V.; Ogale, Satishchandra B.; Han, Sung-Hwan (Electrochemistry Communications, 2009)
Formation of US quantum dots (Q dots) on the vertically aligned ZnO nanorods electrode was carried out by chemical bath deposition. The diameter and thickness of ZnO nanorods are similar to 100-150 nm and similar to 1.6 mu m, respectively, and CdS Q dots on ZnO nanorods have a diameter of smaller than 15 nm. In application of the Q dots-sensitized solar cells, composite film exhibited a power conversion efficiency of 0.54% under air mass 1.5 condition (80 mW/cm(2)), and incident-photon-to-current conversion efficiency showed 18.6%. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical bath deposition; Photosensitization; quantum dots; solar cells; Wet-chemical process

Inhibition effect of N,N-diglycidyl-4-glycidyloxy aniline on photosensitized cationic polymerization of formulations involving resorcinol diglycidyl ether and poly(propylene glycol)diglycidyl ether - Harikrishna, Reghunathan (Journal of Photochemistry and Photobiology A-Chemistry, 2015)
Cationic photopolymerization studies of poly(propylene glycol)diglycidyl ether with and without 25 wt% of resorcinol diglycidyl ether were carried out in presence of bis(4-methylphenyl)iodonium hexafluorophosphate as photoinitiator. Analyses were carried out using polychromatic radiation at different temperatures in a photo differential scanning calorimeter. The formulations showed an enhancement in the rate of polymerization on addition of resorcinol diglycidyl ether. The same formulations when subjected to photosensitized polymerization in presence of 1-chloro-4-propoxy-9H-thioxanthen-9-one, showed a reverse behavior in rate due to partial absorption of radiation by resorcinol diglycidyl ether. Studies carried out on by the addition of N,N-diglycidy1-4-glycidyloxy aniline as inhibitor on the photosensitized formulations showed higher scavenging activity by inhibitor. The addition of nitrogen containing epoxy monomer as inhibitor can lead to its possible crosslinking within the matrix on polymerization along with a decrease in rate of polymerization without compromising on the final observed conversion. This effect can occur readily for non vitrifying systems. Thus, this observation provides an insight into its possible usage in a rate controlled photopolymerizable epoxy formulations. The photopolymerization kinetics were found to depend on the nature of generation, propagation and scavenging of active centers which are heavily dependent on diffusional restrictions imparted by in situ viscosity of the system. The kinetic estimations as well as evaluation of autocatalytic kinetic model are investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Glycidyl ether; Inhibition; kinetic model; kinetics; Photopolymerization; Photosensitization

Enhancing the Catalytic Activity of Pd Nanocrystals towards Suzuki Cross-Coupling by g-C3N4 Photosensitization - Mondal, Sanjit; Sahoo, Lipipuspa; Banoo, Maqsuma; Vaishnav, Yuvraj; Prabhakaran Vinod, Chathakudath; Gautam, Ujjal (Chemnanomat, 2024)
Developing renewable means of activating molecules over traditional catalysts for C-C bond formation is desirable for industrial applications. Herein, we report a strategy to improve the efficiency of Pd nanoparticles (NPs) for the Suzuki cross-coupling reactions by visible-light irradiation using g-C3N4 nanosheets (NSs) as photosensitizer. Pd NPs mounted on g-C3N4 become electron-rich under visible-light due to generation of excited electrons in g-C3N4 and thereby accelerate the rate-determining step. Remarkable photocatalytic activity was accomplished utilizing Pd/g-C3N4 for the Suzuki cross-coupling reaction in environmentally benign aqueous settings under room temperature conditions. The activity remarkably improves (similar to 2.5 times) upon light irradiation, yielding one of the highest known turnover frequencies (TOF) of 1858 h(-1) and confirming the photosensitizer role of g-C3N4. The TOF for coupling of aryl bromides is also significantly high (similar to 356 h(-1)). We establish that the low-energy/long-lived excitons preferencially transfer to Pd, paving a way for rational designing photocatalysts for various C-C coupling reactions.
Keywords: 2D graphitic carbon nitride; C-C cross-coupling; exciton transfer; heterogeneous photocatalyst; Photosensitization